2014
DOI: 10.1155/2014/937203
|View full text |Cite
|
Sign up to set email alerts
|

CNS Involvement in AML Patient Treated with 5-Azacytidine

Abstract: Central nervous system (CNS) involvement in acute myeloid leukemia (AML) is a rare complication of the disease and is associated with poor prognosis. Sometimes the clinical presentation can be unspecific and the diagnosis can be very challenging. Here we report a case of CNS infiltration in a patient suffering from AML who presented with normal complete blood count and altered mental status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The presence of certain factors has been associated with increased risk of neurological complication. These include hyperleukocytosis, high level of lactate dehydrogenase and high expression of CD56 [7]. In a single institution study of 290 pediatric patients with AML, the authors found significant relation between CNS involvement in patients with AML having the cytogenetic abnormality Inv 16, t [9], or AML M4 and M5 subtype.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The presence of certain factors has been associated with increased risk of neurological complication. These include hyperleukocytosis, high level of lactate dehydrogenase and high expression of CD56 [7]. In a single institution study of 290 pediatric patients with AML, the authors found significant relation between CNS involvement in patients with AML having the cytogenetic abnormality Inv 16, t [9], or AML M4 and M5 subtype.…”
Section: Discussionmentioning
confidence: 96%
“…The exact incidence of central nervous system (CNS) involvement in patients with AML is unknown, but is lower compared with the incidence in children and adults with ALL; for that reason routine CSF examination is not performed as part of the diagnostic workup in asymptomatic patients [6,7]. Involvement of the CNS may result acutely from the disease at the diagnosis, as in the index case; from relapse of the disease or from complications of agents used in treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients presenting with altered mental status, headache, visual disturbances, or other neurological symptoms, consideration should be made for leptomeningeal involvement. This is significant because leptomeningeal AML is associated with a poor prognosis and decreased rate of complete response, decreased disease-free survival, and decreased overall survival compared to absence of leptomeningeal disease [ 4 , 7 ]. The incidence of AML with central nervous system (CNS) involvement is lower than that of acute lymphoblastic leukemia (ALL), and thus routine lumbar puncture is not performed in the absence of neurological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of AML with central nervous system (CNS) involvement is lower than that of acute lymphoblastic leukemia (ALL), and thus routine lumbar puncture is not performed in the absence of neurological symptoms. Disease relapse can sometimes occur from the CNS prior to relapse from the bone marrow [ 7 ]. It has been postulated that CNS prophylaxis for AML can improve survival, but this strategy is currently not used given the relatively low incidence of CNS involvement.…”
Section: Introductionmentioning
confidence: 99%